Let 11x + 15y + 23 = 0 be equation (1)
And 7x - 2y - 20 = 0 be equation (2)
Multiply equation (1) by 2:
22x + 30y + 46 = 0
Multiply equation (2) by 15:
105x - 30y - 300 = 0
Add equations (1) and (2):
22x + 105x + 30y - 30y + 46 - 300 = 0
127x - 254 = 0
127x = 254
x = 254/127
[x = 2]
Substitute x = 2 in equation (1) to find y:
11(2) + 15y + 23 = 0
22 + 15y + 23 = 0
15y + 45 = 0
15y = -45
y = -45/15
y = -3
Therefore, x = 2 and y = -3.
<u>a = b + c/d</u>
Subtract 'b' from each side: a - b = c/d
Multiply each side by 'd' : <em>d (a - b) = c
</em>
Answer:
Heres the anwser my man 128
Step-by-step explanation:
hope you got it right.